National mapping of municipality-based rehabilitation services for patients recovering from COVID-19 in Denmark: a cross-sectional study. (2nd November 2022) - Bloomquist, Kira; Tang, Lars H; Kjelsbak, Sissel; Hansen, Linea L; Christensen, Jan
Abstract : Background/aims: A lack of knowledge exists as to how municipalities are meeting the rehabilitation needs of patients recovering from COVID-19. This poses a potential barrier when referring patients for rehabilitation. The aim of this study was to map and describe municipality-based rehabilitation services for patients recovering from COVID-19 in Denmark. Methods: This was a cross-sectional, nation-wide survey. Key staff members from all 98 municipalities in Denmark were invited to participate. Participants had insight into the organisation and professional content of municipal rehabilitation. Structured telephone interviews were conducted by three interviewers between October and November 2020. The interview guide consisted of items that asked about the availability, content and organisation of municipality-based rehabilitation services. Results: A total of 91 municipalities (93% response rate) participated in the study. Rehabilitation could be provided within pre-existing services in 98% of municipalities and 93% systematically assessed individual rehabilitation needs using a variety of measurement methods. All municipalities reported that they had services in place to provide functional rehabilitation (eg gait training) and over 90% provided physical, cognitive and lifestyle-related rehabilitation. In contrast, 70% could provide COVID-19 education and 64% psychological therapy. Overall, 32% of municipalities had not received referrals for COVID-19 rehabilitation. Of the 62 municipalities that had COVID-19 rehabilitation experience, 73% rated the degree to which they could deliver coherent and coordinated rehabilitation for patients with complex rehabilitation needs as high or very high. Conclusions: Overall, Danish municipalities reported that pre-existing services are in place to provide relevant, individualised rehabilitation for patients recovering from COVID-19. Nonetheless, future efforts should ensure that patient education is established, in step with health care providers accumulating knowledge, as well as integrated referral pathways between sectors, to deliver rehabilitation to patients with complex needs. Further, implementation of a national data collection strategy would strengthen and inform future development of relevant services both nationally and internationally.